Probing Multiscale Disorder in Pyrochlore and Related Complex Oxides in the Transmission Electron Microscope: A Review - Wardini, Jenna L.; Vahidi, Hasti; Guo, Huiming; Bowman, William J. (Frontiers in Chemistry, 2021)
Transmission electron microscopy (TEM), and its counterpart, scanning TEM (STEM), are powerful materials characterization methods capable of probing crystal structure, elemental distribution and composition, charge distribution, electronic structure, and bonding down to the atomic scale. Recent (S)TEM instrumentation developments such as electron beam aberration-correction as well as faster and more efficient signal detection systems, have given rise to new and more powerful experimental methods. These advancements have facilitated the capture of high-dimensional datasets containing spatially resolved maps of detailed structural and spectroscopic information. Noteworthy among them are scanning electron nanodiffraction (so-called 4D-STEM), high-count-rate energy-dispersive X-ray spectroscopy (EDXS), as well as direct-detection and vibrational electron energy-loss spectroscopy (EELS). The variety of analytical methods available in the modern (S)TEM makes it ideal for studying systems that reside on a continuum of chemical and spatial ordering, from fully crystalline, chemically ordered states to fully amorphous, chemically disordered states, spanning a range of locally ordered/disordered states. These systems are thus insufficiently characterized by volume-averaged crystallographic and stoichiometric descriptors which cannot provide structural and chemical state on the length scales of short and medium range ordering phenomena. (S)TEM allows us to resolve this order-disorder continuum, enabling more informative structural classifications for systems where small variations in structural or chemical ordering can have a drastic impact on functional properties (e.g., pyrochlores, fluorites, perovskites, and other complex oxides). In this review, we provide a brief introduction to various (S)TEM techniques that are well-suited for analyzing these complex systems. Applications of these techniques to various complex oxide systems (pyrochlores, fluorites, perovskites, etc.) from the literature will be reviewed to demonstrate their capabilities and limitations in resolving the continuum of structural and chemical ordering in complex oxide systems.